Efficiency of Thematic Mapper Data for Detecting the Changes of Land Use -Land Cover in Mosul Lake and Surrounding Area Northern Iraq - Hadi, Firas A.; Ahmad, Walid A.; Mahmood, Faleh Hassan (Iraqi Journal of Science, 2019)
The study area lies in the northern part of Iraq, This study depends on one scene of Thematic Mapper (TM5) data of Landsat, these data are subset by using region of interest (ROI) file within the ERDAS 9.2 software. RS and GIS have been used as tools for detecting the desertification during the periods 1990-2000-2009 by using Normalized Difference Vegetation Index NDVI, Water Index WI and Barren Land Index BLI. The indicators of Desertification which used in this study for period 1990-2000 and 2000-2009 are represented by decrease the vegetation cover and increase water body and barren land.